The Assessment of Student Performance in the Practicum Activity of Basic Physics Course - Yuberti Yuberti; Diana Nomida; Tuti Nuriah (TARBIYA: Journal of Education in Muslim Society, 2016)
Abstract This study was aimed at obtaining factual information on 1) the assessment of Basic Physics course learning achievement of Physics Education students of the Tarbiyah and Teacher Training Faculty of IAIN Raden Intan Lampung that includes process and product assessment and 2) the results of the implementation of assessment on student performance during the practicum component of the course. The study employed Elliot’s Model of Action Research Study, which is a mixed method in nature. It focused on improving instructional condition as the responsibility of the respective lecturer to make it more responsive to the existing needs .Indeed, it requires commitment of all parties involved in the instructional process to participate and collaborate for improved learning achievement, particularly of the Basic Physics course, to be obtained. In conclusion, based on the process and findings of the action research study, the implementation of performance assessment has significantly improved student learning achievement in the Basic Physics course.Abstrak Penelitian ini bertujuan untuk mendpatkan informasi faktual mengenai 1) penilaian hasil belajar Fisika Dasar Pendidikan Fisika Fakultas Tarbiyah dan Keguruan IAIN Raden Intan Lampung yang meliputi penilaian proses dan kinerja, dan 2) hasil implementasi penilaian prestasi mahasiswa selama praktikum. Penelitian menggunakan Penelitian Tindakan Kelas Model Elliot, yang merupakan metode campuran. Penelitian fokus kepada peningkatan kondisi pembelajaran sebagai tanggungjawab dosen yang bersangkutan untuk membuatnya lebih responsif dengan kebutuhan yang ada. Tentunya, hal ini membutuhkan komitmen dari seluruh pihak terkait dalam proses pembelajaran untuk berpartisipasi dan berkolaborasi untuk peningkatan hasil pembelajaran, khususnya mata kuliah Fisika Dasar. Dapat disimpulkan, berdasarkan proses dan temuan penelitian tindakan kelas, penerapan penilaian kinerja secara signifikan meningkatkan prestasi belajar mahasiswa pada mata kuliah Fisika Dasar. How to Cite: Yuberti, Nomida, D., Nuriah, T. (2016). The Assessment of Student Performance in the Practicum Activity of Basic Physics Course. TARBIYA: Journal Of Education In Muslim Society, 3(1), 121-130 doi:10.15408/tjems.v3i1.3397. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v2i1.3397